Climate change and crop yield of oats (Avena sativa L.) in Yakutia - L. V. Petrova; L. Yu. Novikova; A. V. Alekseeva; I. G. Loskutov (Труды по прикладной ботанике, генетике и селекции)
Background. Yakutia lies within a risky farming region, where both low temperatures and insufficient moisture are the limiting factors. Oat is the main cereal fodder crop in Yakutia. Climate warming observed in recent decades has been affecting oat cultivation in different climatic areas of Yakutia. The objective of the study was to analyze weather and climate factors affecting oat yield in the republic during the past decade.Materials and methods. The study covered the data of 2014–2021 on the yield of zoned oat cultivars in three Yakutian variety trial sites located in the Central, Transfluvial and Middle Lena agroclimatic zones, and agronomic characteristics of three oat cultivars in the Central zone in 1999–2021. Variance, correlation, and regression analyses were applied.Results and conclusion. The study showed that in 2014–2021 there was a decrease in oat yields in Yakutia. The correlation analysis showed that this was due to climate changes: active warming, and a tendency towards a decrease in precipitation during the oat growing season. The regression analysis of the oat crop structure in the Central Zone in 1999–2021 confirmed that all yield components depended on the moisture availability, and it was the decrease in precipitation that led to a reduction in such indicators as 1000 grain weight, plant height, panicle length, and yield. A significant dependence on humidification conditions indicates the need to continue breeding work towards the development of drought-resistant oat cultivars adapted to the specific agroclimatic environments of Yakutia.